Recent and future vegetation change in the treeline region of Chukotka (NE Russia) inferred from field data, satellite data and modelling - Shevtsova, Iuliia (Dr.) (2022)
Vegetation change at high latitudes is one of the central issues nowadays with respect to ongoing climate changes and triggered potential feedback. At high latitude ecosystems, the expected changes include boreal treeline advance, compositional, phenological, physiological (plants), biomass (phytomass) and productivity changes. However, the rate and the extent of the changes under climate change are yet poorly understood and projections are necessary for effective adaptive strategies and forehanded minimisation of the possible negative feedbacks. The vegetation itself and environmental conditions, which are playing a great role in its development and distribution are diverse throughout the Subarctic to the Arctic. Among the least investigated areas is central Chukotka in North-Eastern Siberia, Russia. Chukotka has mountainous terrain and a wide variety of vegetation types on the gradient from treeless tundra to northern taiga forests. The treeline there in contrast to subarctic North America and north-western and central Siberia is represented by a deciduous conifer, Larix cajanderi Mayr. The vegetation varies from prostrate lichen Dryas octopetala L. tundra to open graminoid (hummock and non-hummock) tundra to tall Pinus pumila (Pall.) Regel shrublands to sparse and dense larch forests. Hence, this thesis presents investigations on recent compositional and above-ground biomass (AGB) changes, as well as potential future changes in AGB in central Chukotka. The aim is to assess how tundra-taiga vegetation develops under changing climate conditions particularly in Fareast Russia, central Chukotka. Therefore, three main research questions were considered: 1) What changes in vegetation composition have recently occurred in central Chukotka? 2) How have the above-ground biomass AGB rates and distribution changed in central Chukotka? 3) What are the spatial dynamics and rates of tree AGB change in the upcoming millennia in the northern tundra-taiga of central Chukotka? Remote sensing provides information on the spatial ...